Utilisation of a cryptic non-canonical donor splice site of the gene encoding PARAFIBROMIN is associated with familial isolated primary hyperparathyroidism. Issue 8 (1st August 2005) - Bradley, K J; Cavaco, B M; Bowl, M R; Harding, B; Young, A; Thakker, R V
Abstract : More than 99% of all splice sites conform to consensus sequences that usually include the invariant dinucleotides gt and ag at the 5′ and 3′ ends of the introns, respectively. We report on the utilisation of a non-consensus (non-canonical) donor splice site within exon 1 of the HRPT2 gene in familial isolated primary hyperparathyroidism (FIHP). HRPT2 mutations are more frequently associated with the hyperparathyroidism-jaw tumour syndrome (HPT-JT). Patients with FIHP were identified to have a donor splice site mutation, IVS1+1 g→a, and the consequences of this for RNA processing were investigated. The mutant mRNA lacked 30 bp and DNA sequence analysis revealed this to result from utilisation of an alternative cryptic non-canonical donor splice site (gaatgt) in exon 1 together with the normally occurring acceptor splice site in intron 1. Translation of this mutant mRNA predicted the in-frame loss of 10 amino acids in the encoded protein, termed PARAFIBROMIN. Thus, these FIHP patients are utilising a ga-ag splice site pair, which until recently was considered to be incompatible with splicing but is now known to occur as a rare (<0.02%) normal splicing variant.